A comparative study of Executive Remuneration practices within the United States and United Kingdom - Martinez-Atkinson, Daniel (2006)
This dissertation uses US and UK company data from 2004/05 to generate measures for 'current' levels of pay sensitivity for top executives between these two countries, taking into account indirect payments, such as options and long-term incentive plans, which often contribute a significant proportion of total executive remuneration. These results are then analysed and form the basis for a discussion which identifies possible causes for the characteristics found within the two countries remuneration policies.